Development and expansion of a pediatric transitional pain service to prevent complex chronic pain - Isaac, Lisa; Rosenbloom, Brittany N.; Tyrrell, Jennifer; Ruskin, Danielle A.; Birnie, Kathryn A. (Frontiers in Pain Research, 2023)
The prevention of chronic pain is a key priority in North America and around the world. A novel pediatric Transitional Pain Service (pTPS) at the Hospital for Sick Children was established to address four main areas of need, which the authors will describe in more detail:(1) provide comprehensive multi-modal pain management and prevention techniques to children at-risk for the development of chronic pain, (2) provide opioid stewardship for children at-risk for chronic pain and their families at home after discharge, (3) facilitate continuity of pain care for children across transitions between inpatient and outpatient care settings, and (4) support caregivers to manage their child's pain at home. The pTPS works with healthcare providers, patients, and their families to address these areas of need and improve quality of life. Furthermore the service fills the gap between inpatient acute pain services and outpatient chronic pain services (accessible only once pain has persisted for >3 months). In pediatric patients who experience pain in hospital and who have been prescribed opioids, discharge to home or rehabilitation may represent a vulnerable time in which pain may persist and during which analgesic requirements may change.